2013
DOI: 10.1037/a0031503
|View full text |Cite
|
Sign up to set email alerts
|

A contextualized view on long-term predictors of academic performance.

Abstract: Several studies show that parents' and teachers' perceptions of children's academic competence are important predictors of children's subsequent academic performance. However, there is a lack of evidence on what precedes these perceptions as well as the dynamics within a comprehensive model. The aim of this study was to investigate the simultaneous influences of child (general intelligence, prohlem behavior) and family (socioeconomic status, migration background) characteristics as well as parents' and teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
2
14
1
Order By: Relevance
“…The general intelligence indices of all four intelligence tests showed significant predictive validity for averaged school grades three years after intelligence assessment, which is in line with previous studies, showing that intelligence is a positive predictor of scholastic achievement (Deary et al, 2007; Gut et al, 2012, 2013; Roth et al, 2015). Therefore, our results support the use of the general intelligence indices of the IDS, RIAS, SON-R 6-40, and WISC-IV in order to make predictions of a child's averaged school grades.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The general intelligence indices of all four intelligence tests showed significant predictive validity for averaged school grades three years after intelligence assessment, which is in line with previous studies, showing that intelligence is a positive predictor of scholastic achievement (Deary et al, 2007; Gut et al, 2012, 2013; Roth et al, 2015). Therefore, our results support the use of the general intelligence indices of the IDS, RIAS, SON-R 6-40, and WISC-IV in order to make predictions of a child's averaged school grades.…”
Section: Discussionsupporting
confidence: 90%
“…However, in a single study, the expected effects may be smaller, as seen, for example, in Gut et al (2012, 2013), for several reasons. In the present study, for instance, the analyzed sample showed slightly higher general intelligence scores than the population and had a narrow range in school grades, which were all in the passing range.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple developmental studies have shown that parent academic expectations in early elementary school predict later child academic achievement (Entwisle et al, 2005; Gut et al, 2013; Sy & Schulenberg, 2005). Most of these studies controlled for confounding factors, such as family SES, and lend credence to the hypothesis that parental expectations influence child academic outcomes over time (Child Trends, 2015).…”
Section: Parent Academic Expectations and Child Academic Performance:mentioning
confidence: 99%
“…Similarly, Gut, Reimann, and Grob (2013) demonstrated that parent academic expectations at school entry predicted children’s grade point averages three years later. Parents with lower incomes and less education typically have lower academic expectations for their children and feel less efficacious in their capacity to help them succeed than do more economically-advantaged parents (Bandura, Barbaranelli, Caprara, & Pastorelli, 2001).…”
Section: Why Study Parent Academic Expectations As Well As Parenting mentioning
confidence: 93%